2014
DOI: 10.1016/j.jarmac.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive load while driving impairs memory of moving but not stationary elements within the environment.

Abstract: The negative impact of cognitive load, such as cell phone conversations, while driving is well established, but understanding the nature of this performance deficit is still being developed. To test the impact of load on awareness of different elements in a driving scene, memory for items within the environment was examined under load and no load conditions. Participants drove through two different scenarios in a driving simulator, were periodically interrupted by a pause in the driving during, and were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…The previously described phenomenon of inattentional blindness during driving in younger adults (Most and Astur, 2007; Blalock et al, 2014; Murphy and Greene, 2015, 2016, 2017a,b; Ericson et al, 2017) was replicated in the current study and was expanded upon by demonstrating the same phenomenon in older adults. Specifically, participants were unaware of inanimate objects on 56% of all trials and animate objects on 25% of all trials (see Table 4).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The previously described phenomenon of inattentional blindness during driving in younger adults (Most and Astur, 2007; Blalock et al, 2014; Murphy and Greene, 2015, 2016, 2017a,b; Ericson et al, 2017) was replicated in the current study and was expanded upon by demonstrating the same phenomenon in older adults. Specifically, participants were unaware of inanimate objects on 56% of all trials and animate objects on 25% of all trials (see Table 4).…”
Section: Discussionsupporting
confidence: 72%
“…For instance, cognitive load can be increased during driving by the introduction of multitasking requirements (e.g., listening/talking, holding information in memory, navigating; Strayer and Johnston, 2001; Strayer et al, 2003, 2013; Horrey and Wickens, 2006; Blalock et al, 2014; Cuenen et al, 2015; Donmez and Liu, 2015; Ebnali et al, 2016; Svetina, 2016; Murphy and Greene, 2017a; Caird et al, 2018; Wechsler et al, 2018) and perceptual load may be introduced by, for example, environmental clutter (e.g., traffic, buildings, signs, pedestrians; Marciano and Yeshurun, 2012, 2015; Stinchcombe and Gagnon, 2013; Ericson et al, 2017; Michaels et al, 2017), or by increasing perceptual task difficulty (e.g., judging maneuverability around closely arranged obstacles; Murphy and Greene, 2015, 2016). Previous studies with younger drivers have demonstrated more instances of inattentional blindness during conditions of higher compared to lower cognitive and perceptual load (e.g., Most and Astur, 2007; Blalock et al, 2014; Murphy and Greene, 2015, 2016, 2017a,b; Ericson et al, 2017; see Murphy et al, 2016 for a review). For instance, Murphy and Greene (2015, 2016) investigated the effects of perceptual load on inattentional blindness by asking drivers to make perceptual gap judgements about whether their car could fit between a row of parked cars while manipulating perceptual difficulty (i.e., clearly too wide/narrow vs. closely approximating the width of the driver’s vehicle).…”
Section: Introductionmentioning
confidence: 99%
“…cell phone use) while driving negatively impacts memory for landmarks (e.g. Blalock et al, 2014 ). It is possible that the increased cognitive load could influence spatial memory and therefore route navigation.…”
Section: Discussionmentioning
confidence: 99%
“…The drivers' ability to remember moving and stationary objects in the environment (i.e., SA) is related to their cognitive load. Cognitive stress was shown to determine memory performance where cognitive load decreases the accuracy of recollection of moving objects [95]. Regarding this, under a high perceptual load drivers are expected to fail noticing, e.g., an unexpected pedestrian [96].…”
Section: Drivers Measures Using Eye-trackingmentioning
confidence: 99%